2017
DOI: 10.1590/1980-57642016dn11-040015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and cognitive performance in aging

Abstract: ABSTRACT.Background.Atherosclerosis in cerebral blood vessels, especially those which compose the Circle of Willis, can lead to reduced supply of oxygen and nutrients to different cortical structures, affecting cognitive function.Objective:To analyze whether cardiovascular risk factors negatively influence cognitive performance in adults and elderly.Methods:One hundred twenty-nine participants of both sexes, aged over 50 years, without cognitive or functional impairment were included. Body mass index (BMI), hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
(30 reference statements)
0
12
0
2
Order By: Relevance
“…Changes in cognitive performances and cardiovascular disorders represent a normal phenomenon of the aging process (Di Carlo et al, 2000;Leritz et al, 2011;Harada et al, 2013). Cardiovascular risk factors, such as smoking, obesity, diabetes mellitus, increased cholesterol, and systemic blood pressure (BP) levels, and an inadequate lifestyle may compromise also cerebral blood flow, which in turn can negatively affect cognitive performance (Takeda et al, 2017). Moreover, the same age-related anatomical and functional cardiac changes, including also the autonomic nervous system (ANS), determine cardiac output alteration, causing cerebral blood flow modulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in cognitive performances and cardiovascular disorders represent a normal phenomenon of the aging process (Di Carlo et al, 2000;Leritz et al, 2011;Harada et al, 2013). Cardiovascular risk factors, such as smoking, obesity, diabetes mellitus, increased cholesterol, and systemic blood pressure (BP) levels, and an inadequate lifestyle may compromise also cerebral blood flow, which in turn can negatively affect cognitive performance (Takeda et al, 2017). Moreover, the same age-related anatomical and functional cardiac changes, including also the autonomic nervous system (ANS), determine cardiac output alteration, causing cerebral blood flow modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the same age-related anatomical and functional cardiac changes, including also the autonomic nervous system (ANS), determine cardiac output alteration, causing cerebral blood flow modulation. This variation could interfere with microcirculation and cause cerebral ischemia, particularly in those brain sites that control the different cognitive domains (Chen et al, 2011;Al-Qudah et al, 2015;Takeda et al, 2017). Past and recent evidence (Camm et al, 1996;Shaffer and Ginsberg, 2017;Singh et al, 2018a,b) support the relevance of ANS study by heart rate variability (HRV) assessment as a tool for the noninvasive analysis of cardiovascular autonomic function.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal analyses evaluating lesion subtypes over time included all MRI scans in RVCL-S patients (those performed with and without standard imaging). Wechsler Adult Intelligence Scale-Revised Digit Symbol Substitution test (DSST) 15,16 , for working memory and processing speed; category fluency [17][18][19] 27,28 , with accuracy confirmed by visual inspection. Segmented brain volumes were normalized to total intracranial volume, to adjust for head size, defined as the sum of gray matter, white matter, and cerebrospinal fluid volumes 29 .…”
Section: A C C E P T E Dmentioning
confidence: 99%
“… 114 - 116 Obesity has been associated with elevated cardiovascular and cortisol responses to acute stress. 124 A meta-analysis showed an association between obesity and increased risk of AD. 114 Approximately 2% of cases of AD worldwide are potentially related to obesity in middle age.…”
Section: Cumulative Effects Of Chronic Stress and Alzheimer’s Diseasementioning
confidence: 99%
“… 114 Another study noted a U-shaped association, i.e., the two ends of BMI (low or high) were statistically and significantly associated with cognitive performance and AD risk. 116 , 124 Some studies have suggested that being overweight or obese in middle age is a risk for later development of cognitive decline and dementia. 116 , 125 One biological pathway hypothesized to link obesity to cognitive impairment is through leptin, a hormone mainly produced by adipocytes which suppresses appetite and regulates energy expenditure.…”
Section: Cumulative Effects Of Chronic Stress and Alzheimer’s Diseasementioning
confidence: 99%